Rapid sequence intubation - GRBA-BUJEVIC, Maja (Halo 194 Scientific Journal of Emergency Medicine, 2025)
In emergency medicine, there is no procedure that is more important than taking care of the airway. Numerous methods have been proposed in the literature that are used in the case of a compromised airway, and one of them is rapid sequence intubation (RSI). By definition, RSI is the coordinated, sequential process of preparing, sedating, and paralyzing a patient at high risk of aspiration of gastric contents to allow for emergency endotracheal intubation (ETI). Pharmacological sedation and paralysis are induced in rapid succession to provide optimal conditions for laryngoscopy and ETI. RSI is an advanced airway management technique used in critically ill and severely injured patients to protect the airways from regurgitation and aspiration of gastric contents. The application of the RSI technique, consisting of 15 steps, was first described by Stept and Safar in 1970. Today, it represents the gold standard for emergency management of the airway during rapid induction of general anesthesia. More recently, RSI is also applied at the prehospital level as an alternative method for managing the airways of patients with impaired consciousness, in whom it is assumed that they have a full stomach and there is a chance for their survival.